A new species of Abarema (Fabaceae) from Brazil - Guerra, Ethiéne; Morim, Marli Pires; Iganci, João Ricardo Vieira (Phytotaxa, 2016)
A new species of Abarema from Brazil is described and illustrated. The new species is endemic to Morro do Chapéu, Chapada Diamantina, in the state of Bahia. Abarema diamantina shares morphological affinities with A. cochliacarpos by having a capitate raceme, strongly lenticelate branches, and median-basal pleurogram. However, there are remarkable vegetative and reproductive morphological characters which distinguish the two taxa. Here a description of the new species and illustrations are presented; a distribution map, and comments highlighting the differences between the closely related species are discussed.